Temporary Agency Work and the Great Recession - Daniel Baumgarten; Michael Kvasnicka (Institute for the Study of Labor (IZA), 2016)
We investigate with German data how the use of temporary agency work has helped establishments to manage the economic and financial crisis in 2008/09. We examine the (regular) workforce development, use of short-time work, and business performance of establishments that made differential use of temporary agency work prior to the crisis. Overall, our results suggest that establishments with a greater use of temporary agency work coped better with the sharp decline in demand and made less frequent use of government-sponsored short-time work schemes.
Keywords: E32; J23; L23; J68; 330; labour demand; employment adjustment; economic crisis; short-time work; temporary agency work; establishment data